Update on biosimilars of granulocyte colony-stimulating factor: when no news is good news - Schulz, Miriam; Bönig, Halvard (Current opinion in hematology, 2016)
With the approval of the first biosimilar granulocyte colony-stimulating factor (G-CSF), biosimilars - copies of therapeutic biologicals whose patent protection has expired - have finally reached the US healthcare market. Its advent is an occasion for a closer look at recent insights into biosimilar G-CSF and an attempt at prognosticating the future (future role) of biosimilars in general.
Gesehen am 26.05.2020